Using a CeO2 quantum dot hole extraction-layer for enhanced solar water splitting activity of BiVO4 photoanodes - Seo, Dong Hyun; Hong, Seo Yeong; You, Tak Hyun; Sivanantham, Arumugam; Cho, In Sun (Chemical Engineering Journal, 2022)
Colloidal CeO2 quantum dots (CeQDs) were synthesized to boost the photoelectrochemical (PEC) water-splitting activity of bulky-crystalline BiVO4 (BVO) photoanode via rapid hole extraction. CeQDs with average sizes of 1.8, 2.3, and 3.0 nm were prepared by adjusting the reaction temperature. They exhibited high crystallinity and dispersibility in an aqueous solution with high stability. Colloidal CeQDs were directly spin-coated onto the BVO, allowing homogeneous and conformal coating of the CeQD layer on the BVO. The resultant CeQD/BVO exhibited a high water-splitting photocurrent density and steady Faradaic efficiency (∼80%). We found that the CeQD layer simultaneously improved the charge-separation efficiency and transfer kinetics. Finally, we demonstrated the highest photocurrent density (4.0 mA/cm2) and Faradaic efficiency (91%) by depositing CoOx cocatalyst on the CeQD/BVO photoanode. Our results showed that the deposition of colloidal QDs is a facile, scalable, and effective method for improving the PEC activity of BVO for efficient solar water splitting.
Keywords: CeO 2; Colloidal quantum dots; Faradaic efficiencies; Hole extraction layers; Hole extractions; Photo-anodes; Photocurrent density; Photoelectrochemical water splitting; Quantum dot layers; Solar water splitting; BiVO4; CeO2; Colloidal quantum dot; Hole extraction; Photoelectrochemical water splitting